John Shaw Neilson: 'Something of a Mystic' (Journal of the Association for the Study of Australian Literature, 2009)
Competing post-Federation representations of mysticism as bold or passive, masculine or effeminate, dogmatic or independent, Australian or foreign, drove the shifting critical notions of this era culminating in the generalist designations of John Shaw Neilson (1872–1942) as Australia’s all-purpose mystical poet. Neilson is a mystical poet; yet the basis for this has been subject to a number of distortions from Neilson’s time until the late 1990s. This article examines how an understanding of both Western Christian mysticism and its often erroneous critical applications in Australia might inform new studies of the mystical Neilson.